Assessing General Aviation Pilots' Understanding of Aviation Weather Products. Issue 3 (2nd October 2017) - Blickensderfer, Beth; Lanicci, John; Guinn, Thomas A.; King, Jayde; Ortiz, Yolanda; Thomas, Robert
ABSTRACT: Objective : The objective of this article was to develop a written examination to assess general aviation (GA) pilots' understanding of aviation meteorology products. Background : Although the number of accidents in GA flight continues to decrease over time, one troubling situation is when pilots encounter hazardous weather. Although research has approached this topic from a variety of perspectives, prior research has not offered a detailed inspection of GA pilots' knowledge about weather concepts and phenomena, weather products, and the implications of weather concepts and products to flight—knowledge that is fundamental for pilots to develop higher order cognitive skills in aviation weather. A valid and reliable assessment tool to measure pilots' knowledge of weather is not available. Method : A multidisciplinary research team developed a 95-item, multiple-choice aviation meteorology test. The questions were based on Federal Aviation Administation guidance on aviation weather and written according to guidelines for assessment instrument development. Initial validation was done with data collected from 204 GA pilots. Results : The results showed that the test had high internal consistency, had varying degrees of item difficulty, and discriminated between pilots with differing levels of expertise. Conclusion : Findings from this study indicate that a written test on the aviation weather concepts necessary for safe flight has promise for use in both research and practice.